Periarticular muscle status affects in vivo tibio-femoral joint loads after total knee arthroplasty - Winkler, Tobias; Bell, Louisa; Bender, Alwina; Trepczynski, Adam; Duda, Georg N.; Baur, Alexander J. D.; Damm, Philipp (Frontiers in Bioengineering and Biotechnology, 2023)
Background Total knee arthroplasty (TKA) is a highly effective treatment for severe knee osteoarthritis that is increasingly performed in younger, more active patients. As postoperative muscular impairments may negatively affect surgical outcomes and implant longevity, functional muscle recovery gains increasing importance in meeting future patient demands. This study aimed to assess the status of periarticular muscles in the long-term follow-up after TKA and to evaluate its impact on in vivo tibio-femoral joint loads. Methods A case series was created, with eight patients with knee osteoarthritis. All subjects received an instrumented knee implant in unilateral TKA. Native computed tomography scans, acquired pre and postoperatively, were used to evaluate distal muscle volumes and fatty infiltration. In vivo tibio-femoral joint loads were measured telemetrically during standing, walking, stair climbing and chair rising and were correlated to muscle status. Results Postoperatively a reduction in fatty infiltration across all periarticular muscles was pronounced. High average peak loads acted in the tibio-femoral joint ranging from 264% during stand-to-sit activities up to 341 % body weight (BW) during stair descent. Fatty infiltration of the m. quadriceps femoris and hamstrings were associated with increased tibio-femoral joint contact forces during walking (r = 0.542; 0.412 and 0.766). Conclusion The findings suggest that a fatty infiltration of periarticular muscles lead to increased tibio-femoral joint contact forces. Improvements in functional mobility and the restoration of a pain-free joint likely explain the observed postoperative reductions in fatty infiltration. Perioperative rehabilitation approaches targeting residual impairments in muscle quality could, hence, contribute to reduced tibio-femoral joint loads and improved long-term outcomes of TKA. However, it has to be pointed out that the study included a small number of patients, which may limit its validity.